MICRONEEDLE ARRAY - TOKUMOTO SEIJI; TERAHARA TAKAAKI; TAMURA AKIRA; YAMADA YUMIKO (2013)
Relations between crystallinity and performance of a biodegradable resin, between weight-average molecular weight and strength thereof, and between weight-average molecular weight and performance thereof were clarified. As a result thereof, when a microneedle array was provided with microneedles containing noncrystalline polylactic acid which had a weight-average molecular weight of 40,000 to 100,000, it was possible to obtain a microneedle array which could maintain its functional performance.